Does vitamin K prophylaxis prevent bleeding in neonates exposed to enzyme-inducing antiepileptic drugs in utero? - Rezvani, Massoud (College of Family Physicians of Canada, 2006)
QUESTION: One of my epileptic patients takes carbamazepine. She is 36 weeks pregnant and has asked me whether she should start vitamin K to prevent neonatal bleeding. Does current evidence support this practice? ANSWER: Recent evidence does not support the notion that newborns of women treated with enzyme-inducing anticonvulsant drugs are at increased risk of hemorrhagic disease. Antenatal vitamin K can be prescribed on an individualized basis in certain circumstances, such as imminent premature delivery.